Recursos didácticos tecnológicos y rendimiento académico, en la asignatura de Química. Año lectivo 2021-2022 - Narvaez Garay, Maryuri Stefany (2022)
Technological and didactic resources are fundamental in the development of the teaching and learning process of the Chemistry subject; for this reason, the present research emerges as a necessity, due to the low academic performance of the students with the purpose of optimize the generation of significant learning in them through the application of technological and didactic resources, the general objective of this research was: to promote the academic performance of students, in the subject of Chemistry, through the design and application of technological and didactic resources, which facilitate the development of the teaching-learning process; in the third course of the Bachillerato General Unificado, of "Beatriz Cueva de Ayora" High School; academic year 2021-2022. The qualitative method was used in the methodology process; because, along the research, from the diagnosis to the intervention and evaluation of results, relevant characteristics were determined around the implementation of technological and didactic resources; among the instruments used for the research are the following: observation matrix, survey questionnaire, interview guide and questionnaires for evaluation; resulting in a positive and significant improvement in the academic performance of students. It was determined that the application of technological and didactic resources through micro - curricular planning, facilitated the development of the teaching and learning process, which enhances the academic performance of the students; this was evidenced in the results obtained through different types of applied evaluations. Keywords: Teaching – learning, technological devices, significative learning, technological tools, constructivism.